Acute central nervous system complications and ammonium levels in adult patients with acute lymphoblastic leukemia receiving l-asparaginase. Issue 4 (3rd April 2018) - Strickler, Nicole; Balabanov, Stefan; Casauro, Katharina; Schanz, Urs; Manz, Markus G.; Gerber, Bernhard
Abstract: We analyzed ammonium levels and acute central nervous complications in adult patients receiving chemotherapy for acute lymphoblastic leukemia with or without asparaginase (l -asp). Twenty patients with a median age of 40.3 years were included. Ammonium-levels were measured during 88 chemotherapy cycles, 60 cycles (68%) withl -asp, and 28 cycles (32%) withoutl -asp. Ammonium was elevated in 87% of alll -asp containing cycles, with median ammonium levels of 169 μmol/l (interquartile range (IQR) 91–269 μmol/l). These values were higher when compared to ammonium levels at baseline (31.5 μmol/l, IQR 24–40 μmol/l, p < .001), and when compared to levels in cycles withoutl -asp (30 μmol/l, IQR 19–41 μmol/l, p < .001). Acute hyperammonemic encephalopathy was diagnosed in one patient, and encephalopathy for other reasons, but with hyperammonemia as a possible contributing factor in four patients. In conclusion, ammonium levels are elevated in all adult patients receivingl -asparaginase, but only some patients will present symptoms of encephalopathy.